Energy, exergy and economic analyses of two modified and optimized small-scale natural gas liquefaction (LNG) cycles using N2 and N2/CH4 refrigerants with CO2 precooling. (September 2019) - Sanaye, Sepehr; Shams Ghoreishi, Seyed Milad
Highlights: Two modified and optimized small LNG cycles are proposed. N2 -CO2 and N2 /CH4 -CO2 with CO2 pre-cooling were optimized for the lowest SEC value. Compared to similar cycles, 5.25% and 3.62% decrease in SE value were observed. The total annual cost of two above cycles also decreased for 0.5% and 1.2%. Their exergy destruction also decreased 9.4% and 16% in two above cycles. Abstract: Natural gas liquefaction cycles require high amounts of shaft power and any effort for decreasing power consumption of these cycles is a subject of interest. Among natural gas liquefaction cycles, N2 and N2 /CH4 cycles with CO2 pre-cooling are attractive due to their simplicity. The novel work here is that two above cycles are first modified. Then by choosing the ratio of power consumption to the liquefied gas molar flow rate (Specific Energy Consumption, SEC) as the objective function and 13 design parameters for N2 -CO2 cycle and 12 design parameters for N2 /CH4 -CO2 cycle, these cycles are optimized. Results of the above procedure showed decrease in both SEC and the total annual cost in comparison with those for similar cycles published in open literature. Two modified and optimized N2 -CO2 and N2 /CH4 -CO2 liquefaction cycles showed 5.25% and 3.62% decrease in specific energy consumption and 9.4% and 16% decrease in exergy destruction respectively. The total cost of two above cycles also decreased for 0.5% and 1.2% respectively.